Considerations on three pre-Roman place names from southern Portugal (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2021)
Linguistic arguments allow us to think that Ossonoba, Murtili and Baesuri belong to the same pre-Roman toponymy as that of neighboring Andalusia. The fact that they are Latinized forms is not an obstacle to this.
Keywords: Ossonoba; Murtili; Baesuri; Pre-Roman toponymy of Hispania